Effect of a Multistage Educational Skill-Based Program on Nurse’s Stress and Anxiety in the Intensive Care Setting: A Randomized Controlled Trial - Mohsen Saffari; Farshid Rahimi Bashar; Amir Vahedian-Azimi; Mohamad Amin Pourhoseingholi; Leila Karimi; Morteza Shamsizadeh; Keivan Gohari-moghadam; Amirhossein Sahebkar (Behavioural Neurology)
Background. Psychological problems such as stress and anxiety are prevalent among working nurses in the intensive care units (ICUs). This study was aimed at investigating the effects of three skill-based educational programs on stress and anxiety among critical care nurses. Methods. Using a randomized controlled trial, 160 nurses were assigned to four groups including one control and three intervention groups. A standard skill-based educational program was delivered to three intervention groups using booklet, booklet+oral presentation, and booklet+oral presentation+clinical teaching over a period of one month to reduce different types of stress and anxiety. The control group received routine education only. Perceived stress, state anxiety, trait anxiety, and work-related stress were assessed at baseline and three times after the intervention (15 days, 3 months, and 21 months). Repeated-measure analysis of variance was used for data analysis. Results. There was no significant change in the control group in terms of study variables during follow-up assessments, whereas measures of stress and anxiety were reduced after intervention in the trial groups except trait anxiety. Nurses in the mixed-method group (booklet+oral presentation+clinical teaching) showed less stress and anxiety during follow-ups. Although the stress and anxiety scores decreased in the first and second follow-ups, there was no significant reduction in the third follow-up. Conclusions. To improve the mental health and performance of the intensive care unit nurses, knowledge-based and skill-based training programs seem useful. Continuous training may help to maintain the effectiveness of these programs over time.